Structural study of the partially disordered full-length δ subunit of RNA polymerase from Bacillus subtilis - Papoušková, Veronika; Kadeřávek, Pavel; Otrusinová, Olga; Rabatinová, Alžbeta; ŠSanderová, Hana; Nováček, Jiří; Krásný, Libor; Sklenář, Vladimír; Žídek, Lukáš (Chembiochem, 2013)
The partially disordered δ subunit of RNA polymerase was studied by various NMR techniques. The structure of the well-folded N-terminal domain was determined based on inter-proton distances in NOESY spectra. The obtained structural model was compared to the previously determined structure of a truncated construct (lacking the C-terminal domain). Only marginal differences were identified, thus indicating that the first structural model was not significantly compromised by the absence of the C-terminal domain. Various (15) N relaxation experiments were employed to describe the flexibility of both domains. The relaxation data revealed that the C-terminal domain is more flexible, but its flexibility is not uniform. By using paramagnetic labels, transient contacts of the C-terminal tail with the N-terminal domain and with itself were identified. A propensity of the C-terminal domain to form β-type structures was obtained by chemical shift analysis. Comparison with the paramagnetic relaxation enhancement indicated a well-balanced interplay of repulsive and attractive electrostatic interactions governing the conformational behavior of the C-terminal domain. The results showed that the δ subunit consists of a well-ordered N-terminal domain and a flexible C-terminal domain that exhibits a complex hierarchy of partial ordering.
Keywords: Bacillus subtilis; DNA-Directed RNA Polymerases; Recombinant Proteins; DNA řízené RNA-polymerasy; Bacterial Proteins; Protein Structure, Tertiary; terciární struktura proteinů; δ subunit; Static Electricity; molekulární sekvence - údaje; Amino Acid Sequence; protein structures; Protein Subunits; sekundární struktura proteinů; Protein Structure, Secondary; podjednotky proteinů; rekombinantní proteiny; RNA polymerase; partially disordered proteins; statická elektřina; nukleární magnetická rezonance biomolekulární; bakteriální proteiny; sekvence aminokyselin; NMR spectroscopy; Molecular Sequence Data; Nuclear Magnetic Resonance, Biomolecular